PHARMACOGNOSTICAL, PHYSICOCHEMICAL AND HPTLC EVALUATION OF AMRUTADHYA GUGGULU A POLYHERBAL FORMULATION FOR PHARMACEUTICAL STANDARDIZATION - Zala, Divya; Dilip Prajapati; Anup Thakar; Harisha CR; V.J.Shukla (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Standardization of herbal formulation is needed in order to assess of quality of drug. Maintaining the quality standard of a polyherbal formulation is a difficult task. In the era of increasing demand for traditional medicines, maintaining quality standards is the need of the hour.Aim: The present work was carried out to standardize the finished product Amrutadhya Guggulu to confirm its identity, quality and purity.Material and Method: Amrutadhya Guggulu is mentioned in the treatment of Sthaulya (Obesity), and it was prepared according to the method as described in Chakradatta. Amrutadhya Guggulu powder was evaluated for its pharmacognostic and pharmaceutical analysis. It contains drug like Guduchi, Ela, Kutaja Phala, Kutaj twaka etc.Result: Epicarp and stone cell of Vidanga, silica deposition of Amalaki, oil globule of Ela etc were the characteristic features observed in the microscopy of Amrutadhya Guggulu powder .Results found in pharmaceutical parameters of Amrutadhya Guggulu powder like Loss on drying8.07% w/w, Ash value 3.07% w/w, Water soluble extract 22.5 % w/w, alcohol soluble extract 13.44%w/w and pH 4Conclusion: The Obtained values of all parameters for the finish product can be adopted to set down new standards.Keywords:  Amrutadhya Guggulu, HPTLC, Pharmacognostical, Pharmaceutical analysis